Recanalization of bilateral axillaris/brachialis artery occlusion in a patient with Takayashu arteritis: First case report on using a novel drug‐coated nitinol "chocolate" balloon catheter. Issue 12 (5th November 2018) - Leigh, Mariatu Binta; Kor, Samad; Czantrak, Petar; Sacirovic, Mesud; Pagonas, Nikolaos; Hillmeister, Philipp; Zeidler, Gabriele; Bramlage, Peter; Buschmann, Ivo
Key Clinical Message: When fibrosis develops in Takayasu arteritis (TA), endovascular treatment may become necessary. A 63‐year‐old woman with TA underwent PTA with a nitinol‐structured (chocolate‐like) drug‐coated balloon (C‐DEB PTA). She remained in remission for >1 year. The case may foster research into the use of C‐DEB PTA in TA. Abstract : When fibrosis develops in Takayasu arteritis (TA), endovascular treatment may become necessary. A 63‐year‐old woman with TA underwent PTA with a nitinol‐structured (chocolate‐like) drug‐coated balloon (C‐DEB PTA). She remained in remission for >1 year. The case may foster research into the use of C‐DEB PTA in TA.